Health-related quality of life after colorectal cancer in England: a patient-reported outcomes study of individuals 12 to 36 months after diagnosis - Downing, Amy; Morris, Eva J.A.; Richards, Mike; Corner, Jessica; Wright, Penny; Sebag-Montefiore, David; Finan, Paul; Kind, Paul; Wood, Charlotte C.; Lawton, Sarah; Feltbower, Richard; Wagland, Richard; et al. (American Society of Clinical Oncology, 2015)
Purpose: This population-level study was conducted to define the health-related quality of life (HRQL) of individuals living with and beyond colorectal cancer (CRC) and to identify factors associated with poor health outcomes. Patients and Methods: All individuals diagnosed with CRC in England in 2010 and 2011 who were alive 12 to 36 months after diagnosis were sent a questionnaire. This included questions related to treatment, disease status, other long-term conditions (LTCs), generic HRQL (EuroQol-5D), and cancer-specific outcomes (Functional Assessment of Cancer Therapy and Social Difficulties Inventory items). Results: The response rate was 63.3% (21,802 of 34,467 patients). One or more generic health problems were reported by 65% of respondents, with 10% of patients reporting problems in all five domains. The reporting of problems was higher than in the general population and was most marked in those age less than 55 years. Certain subgroups reported a higher number of problems, notably those with one or more other LTCs, those with active or recurrent disease, those with a stoma, and those at the extremes of the age range (< 55 and > 85 years). Of respondents without a stoma, 16.3% reported no bowel control. Reversal of a stoma resulted in fewer severe bowel problems but more moderate problems than those who had never had a stoma. A quarter of rectal cancer respondents (25.1%) reported difficulties with sexual matters (compared with 11.2% of colon cancer respondents). Conclusion: This study demonstrates the success of a national patient-reported outcomes survey. The results have the potential to support system-wide improvement in health outcomes through the identification of particular challenges faced by individuals after treatment for CRC.